Minimum energy control of fractional positive continuous-time linear systems with bounded inputs - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
A minimum energy control problem for fractional positive continuous-time linear systems with bounded inputs is formulated and solved. Sufficient conditions for the existence of a solution to the problem are established. A procedure for solving the problem is proposed and illustrated with a numerical example.
Keywords: fractional systems; positive systems; minimum energy control; bounded inputs